DIVERSIFIKASI OLAHAN LELE SEBAGAI STRATEGI PENINGKATAN DAYA SAING PRODUK UMKM - Iqbal, Muhammad; Yuma, Febby Madonna; Nurhasanah, Nurhasanah; Sembiring, Muhammad Ardiansyah (Smart Education, 2025)
Abstract: This community service initiative aims to enhance the economic value and competitiveness of the POKDAKAN Tani Makmur fish farmer group in Asahan Regency through catfish product diversification and digital marketing. The main problems identified include dependency on fresh fish sales and reliance on middlemen for distribution. The proposed solutions involve training on producing three processed products (nuggets, meatballs, and catfish chips), vacuum packaging techniques, and E-CRM-based marketing via WhatsApp Business and TikTok Shop. The program was implemented in five stages: socialization, technical training, technology application, mentoring and evaluation, and program sustainability. Initial results showed a 8 kg/day increase in processed product output, the activation of three online marketing platforms, and the development of a digital point-based customer loyalty system. The outcomes indicate that a technology-driven and participatory training approach can increase income, expand market reach, and support the digital transformation of community-based aquaculture businesses. This activity supports several SDGs, particularly food security, poverty alleviation, and inclusive economic growth. Keyword: catfish; digital marketing; E-CRM; product diversification; MSMEs. Abstrak: Pengabdian ini bertujuan meningkatkan daya saing ekonomi POKDAKAN Tani Makmur di Asahan melalui diversifikasi produk lele dan pemasaran digital. Masalah utama mitra adalah ketergantungan pada lele segar dan distribusi yang dikuasai tengkulak. Solusi mencakup pelatihan olahan lele (nugget, bakso, keripik), pengemasan vakum, dan promosi melalui WhatsApp Business dan TikTok Shop berbasis E-CRM. Metode kegiatan terdiri dari sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan evaluasi. Hasil menunjukkan peningkatan produksi olahan hingga 8 kg/hari, terbentuknya tiga kanal pemasaran digital aktif, dan sistem poin pelanggan digital. Evaluasi berbasis omzet dan pertumbuhan pelanggan digital menunjukkan keberhasilan pendekatan pelatihan berbasis teknologi dan partisipatif. Program ini terbukti memperluas pasar, meningkatkan pendapatan, dan mendukung transformasi digital UMKM perikanan. Kegiatan ini mendukung SDGs dalam ketahanan pangan dan pertumbuhan ekonomi inklusif.. Kata kunci: diversifikasi produk; E-CRM; ikan lele; pemasaran digital; UMKM.